Impact of skeletal muscle loss and sarcopenia on outcomes of neoadjuvant immunochemotherapy in esophageal squamous cell carcinoma - Xu, Binwen; Liu, Junhong; Zhang, Yue; Luo, Tao; Xiong, Jie; Wang, Hanxiao; Shi, Guidong; Fu, Maoyong (Frontiers in Nutrition, 2025)
BackgroundSarcopenia is a systemic disorder characterized by the progressive loss of skeletal muscle mass and function; however, its impact on the treatment outcomes of patients with esophageal cancer remains inconclusive. We aimed to evaluate the impact of sarcopenia and dynamic changes in skeletal muscle during treatment on neoadjuvant immunochemotherapy (NICT) efficacy and prognosis in patients with locally advanced ESCC.MethodsWe retrospectively included 272 patients with locally advanced ESCC who received NICT. We calculated the skeletal muscle index (SMI) and its rate of change (ΔSMI%) from CT images at the L3 vertebral level obtained before and after treatment. Sarcopenia was defined as an SMI < 52.4 cm2/m2 in men and <38.5 cm2/m2 in women, and a ΔSMI% < −2.8% was designated as excessive skeletal muscle loss.ResultsThe prevalence of sarcopenia increased from 50.9% before treatment to 55.1% at therapy completion. Pre-NICT sarcopenia correlated with tumor progression (p = 0.02) and was associated with a significantly lower pathological complete response (pCR) in patients who had sarcopenia than in those without (14.7% vs. 25.0%, p = 0.04). Patients with tumor progression had a significantly lower SMI than those in the disease-control group (41.6 ± 7.24 vs. 48.71 ± 8.39, p = 0.04). In a subgroup analysis of excessive skeletal muscle loss, these patients experienced higher hematologic toxicity (leukopenia: 33.4% vs. 20.9%, p = 0.04; anemia: 70.7% vs. 50.6%, p = 0.01) and lower pCR rate (12.0% vs. 22.8%, p = 0.05). After a median follow-up of 20.4 months, sarcopenia before or after NICT did not significantly affect overall survival (OS) or disease-free survival (DFS) (p > 0.05). Conversely, excessive skeletal muscle loss during treatment emerged as an independent prognostic factor for OS in multivariate analysis (HR = 0.47; 95% CI, 0.25–0.91; p = 0.03); however, it was not associated with DFS (p = 0.22).ConclusionTreatment-induced excessive skeletal muscle loss may serve as a predictive marker for NICT toxicity and short-term survival in patients with locally advanced ESCC, highlighting the need for dynamic nutritional monitoring to optimize treatment tolerance.